Validity of Socio-Scientific Issues (SSI) Based Student Worksheets on Environmental Change Material to Train Reflective Judgment Ability - Ummah, Inayatul; Susantini, Endang (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2025)
Reflective judgement is the ability to evaluate and process information to reach conclusions based on the data collected. Students who have good reflective judgment skills are more capable in solving complex problems. Students can explore various solutions, consider the consequences of each solution, and make better decisions based on critical and systematic analysis. An approach that can be applied in learning to train reflective judgment skills is the SSI approach. Learning using the Socio-Scientific Issues (SSI) approach seeks to engage students in decision-making about current social issues that have a moral impact in a scientific context. The purpose of the research is to produce Students' Worksheets based on the SSI of environmental change topic to train reflective judgment that are valid, practice, and effective. This research is a development research consisting of analysis, design, development and evaluation stages. This research produced Students' Worksheets contains two learning activities and features that are in accordance with SSI aspects. The Bio-News feature contains articles about the Earthquake on Bawean Island and the Operation of the Cement Factory which students will then explore with the Bio-Explore, Bio-Disscus features, and in the Bio-Evaluate feature students make problem solving decisions on the articles presented. The validation results based on aspects of content feasibility, presentation feasibility, language feasibility, and aspects of practicing reflective judgment ability amounted to 3.86, categorized as very valid.